Acinetobacter Plasmids: Diversity and Development of Classification Strategies - Mindlin, Sofia; Beletsky, Alexey; Rakitin, Andrey; Mardanov, Andrey; Petrova, Mayya (Frontiers in Microbiology, 2020)
Bacteria of the genus Acinetobacter, with their numerous species common in various habitats, play a significant role as pathogens. Their ability to adapt to different living conditions is largely due to the presence of numerous plasmids containing the necessary adaptive genes. At the same time the diversity of Acinetobacter plasmids and their evolutionary dynamics have not been sufficiently studied. Here, we characterized 44 plasmids isolated from 5 permafrost A. lwoffii strains, examined their relationship with plasmids of modern Acinetobacter strains and identified groups of related plasmids. For this purpose, we have developed a combined approach for classifying all known Acinetobacter plasmids. The classification took into account the size of plasmids, the presence and structure of the rep and mob genes, as well as the structure of their backbone and accessory regions. Based on the analysis, 19 major groups (lineages) of plasmids were identified, of which more than half were small plasmids. The plasmids of each group have common features of the organization of the backbone region with a DNA identity level of at least 80%. In addition, plasmids of the same group have similarities in the organization of accessory regions. We also described a number of plasmids with a unique structure. The presence of plasmids in clinical strains that are closely related to those of environmental permafrost strains provides evidence of the origin of the former from the latter.